(3+2L)-2+2L=48

Simple and best practice solution for (3+2L)-2+2L=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3+2L)-2+2L=48 equation:


Simplifying
(3 + 2L) + -2 + 2L = 48

Remove parenthesis around (3 + 2L)
3 + 2L + -2 + 2L = 48

Reorder the terms:
3 + -2 + 2L + 2L = 48

Combine like terms: 3 + -2 = 1
1 + 2L + 2L = 48

Combine like terms: 2L + 2L = 4L
1 + 4L = 48

Solving
1 + 4L = 48

Solving for variable 'L'.

Move all terms containing L to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 4L = 48 + -1

Combine like terms: 1 + -1 = 0
0 + 4L = 48 + -1
4L = 48 + -1

Combine like terms: 48 + -1 = 47
4L = 47

Divide each side by '4'.
L = 11.75

Simplifying
L = 11.75

See similar equations:

| y-2=4+2 | | -6(-4p-8)+6(1-6p)=78 | | c+2c-5-5=7 | | 3n-1=8 | | 2(6-8b)=22-6b | | 6x+26x-8=8(4x+10) | | 4j-36=7j | | 6.8+1.2n=4.28 | | 8r^2+26r-7=0 | | 5(7v+8)=4-v | | (y-4)(y-4)-2y=0 | | -20t+-28=32 | | 3n=1.333 | | 7a-3=3+6 | | C=.25f(r+b) | | 14-y=2y+19 | | 3x+13x-9=4(4x+8) | | 4x+2+3x=8x+4 | | 3x-3=3(7-x) | | (7s+3)(4s-12)=0 | | 1/3=12/36 | | 15m-18=6m+4 | | x^2+18=-6x | | 5*-1-4x=x+7 | | x-.6=5-.2x | | 5j+s=2 | | 250/125=x/5 | | -11+n+8-n=n-5+7 | | 0.52+0.49t=1.81t-0.36 | | a^4-21=7 | | 5y-2=53 | | -3n+5=-2n-1 |

Equations solver categories